1999
DOI: 10.1115/1.483140
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Management Strategies for Embedded Electronic Components of Wearable Computers

Abstract: Wearable computers are rugged, portable computers that can be comfortably worn on the body and easily operated for maintenance applications. The recently developed process of Shape Deposition Manufacturing has created the opportunity to embed the electronics of wearable computers in a polymer composite substrate. As both a protective outer case and a conductive heat dissipating medium, the substrate satisfies two basic constraints of wearable computer design: ruggedness and cooling efficiency. One such applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…However, high thermal dissipation associated with these chips requires more studies on how to effectively maintain their temperatures below the maximum operating temperature for safe operating conditions [1]. An excessive amount of heat could be sufficient to melt or to change the thermo-physical properties of chips, affecting their reliability and functionality [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, high thermal dissipation associated with these chips requires more studies on how to effectively maintain their temperatures below the maximum operating temperature for safe operating conditions [1]. An excessive amount of heat could be sufficient to melt or to change the thermo-physical properties of chips, affecting their reliability and functionality [2].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that due to higher thermal conductivity of PCM sheets than PE sheets, the rise in temperature for outer case was less thus causing less discomfort to the user. Haoshan Ge [7] [11]., (2000), in order to understand the thermal phenomena of embedded electronics design and to explore the thermal design space, analyzed the finite element numerical simulations, physical experimentation, and analytical models. The results show that the exposed surface area of the heat spreader and the conductivity of the substrate are the most important parameters affecting the thermal performance of the embedded electronic artifact.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a better understanding is needed of the shrinkage behavior of thermoplastic polymers in molding in order to utilize emerging molding concepts, such as multi-stage multi-material molding, embedding of electronic components, and use of advanced polymer composites [1][2][3][17][18][19]. For example, shrinkage of a polymer around an embedded electronic component during processing induces residual stresses that accelerate fatigue [17]. Also, in a multi-stage molding process, polymers are molded on top of each other altering the interaction between the mold and polymer melts [5].…”
Section: Introductionmentioning
confidence: 99%